2015
DOI: 10.3116/16091833/16/3/111/2015
|View full text |Cite
|
Sign up to set email alerts
|

High-power table-top white-light few-cycle laser generator

Abstract: Abstract.We have achieved experimentally a generation of white-light few-cycle femtosecond laser pulses, using a neon-filled hollow-core fibre. The pulses observed by us are as short as 6.22 fs at the repetition rate of 1 kHz, when the input is characterized by the parameters 2.5 mJ and 33 fs. Pulse compression has been achieved using a supercontinuum produced in a static neon-filled hollow fibre, while a pair of chirped mirrors have compensated the dispersion. Our technique allows for directly tuning the puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, by replacing the AO Q-switch with a saturable absorber, the mode-locking can be obtained, and the pulse width can be reduced to several hundred picoseconds. Although previous studies have shown that ultrafast high-power HG mn laser beams are affected by other parameters like self-phase modulation and bandwidth [25,26], the relatively large dimensions of the gain medium, such as a slab with a large aspect ratio, will reduce the effect. Further conversion to vortex LG pl modes can be achieved by using AMC composed of cylindrical lenses, which will be widely used in optical communication, material processing, and many other fields [27][28][29].…”
Section: Power Scaling In Mopa System Using Cascaded Slab Modulementioning
confidence: 98%
“…Meanwhile, by replacing the AO Q-switch with a saturable absorber, the mode-locking can be obtained, and the pulse width can be reduced to several hundred picoseconds. Although previous studies have shown that ultrafast high-power HG mn laser beams are affected by other parameters like self-phase modulation and bandwidth [25,26], the relatively large dimensions of the gain medium, such as a slab with a large aspect ratio, will reduce the effect. Further conversion to vortex LG pl modes can be achieved by using AMC composed of cylindrical lenses, which will be widely used in optical communication, material processing, and many other fields [27][28][29].…”
Section: Power Scaling In Mopa System Using Cascaded Slab Modulementioning
confidence: 98%